The body as an argumentative metaphor in Our America, by José Martí - Avalos Florez, Edison Duvan (Revista Ecos de la Academia, 2023)
This essay proposes reading Nuestra América, by José Martí, based on a metaphorical construction that runs through the text: the American continent is a consciousness that simultaneously inhabits two bodies, one sick and the other healthy. The sick body, which represents the Colony, is characterized by suffering pain and being monstrous; the healthy body, which represents the Republic, is characterized by having a strong pride that is born from self-knowledge. This metaphorical construction, beyond reflecting the tension of powers experienced during Independence, shows that in Martí’s political imaginary the Colony and the Republic were not historical periods but states of the subject. In the same way, America, in that imaginary, was not a geographical space but a divided culture that suffered from a fatigue of accommodation produced by the antagonistic struggle between good and evil. Although this metaphorical construction seems to have a positivist character, the truth is that at no time is it used to despise the differences or racial crossovers present in America; on the contrary, it is used to warn of the social decomposition that the continent can suffer due to the absence of values.